Diagnosis of IgA nephropathy by immunohistochemical methods using formalin fixed paraffin embedded sections - Angunawela, P.; Sheriff, M.H.R.; Anapalahan, M.; Rajakanthan, K.; Nanayakkara, S.; De Mel, W.C.P. (My University, 1991)
The technique of immunofluorescence to demonstrate immunoglobulins complement and fibrinogen is of proven value in the diagnosis of several renal conditions. The disadvantages of this procesure are the requirement of fresh frozen tissue, the cryostat and immunofluorescence microscope and the inability to have permanent preparetaions. All of these disadvantages would be avoided if formalin fixed paraffin embedded tissues could be used for immunohistochemistry. Ten cases of renal biopsies of patients who presented with haematuria, and mild proteinuria were selected over a period of 10 months. Both sexes were included and the age raged from 12 to 44 years. The biopsies were fixed in formalin and embedded in paraffin and routine stains were performed. Immunohistochemical stains were done by avidinbiotin complex method using polyclonal antisera. Histologically the biopsies showed minimal change and mesangioproliferative glomerulonephritis. Immunohistochemistry showed granular deposits in the mesangial matrix with IgA and c3, in four patients. When compared with immunofluorescence pictures of IgA positive control, the immune complex deposits appeared granular in both and they were presents in the mesangial matrix. The present results show that it is possible to use the technique of immunohistochemistry tom demonstrate immunoglobulins in formalin fixed paraffin embedded renal tissue.